Relación del síndrome metabólico con la periodontitis: una revisión sistemática (2018)
Objective: analyze the relationship between Metabolic Syndrome and Periodontitis through a systematic review.Materials and methods: a systematic review supported on scientific articles mainly of case-control studies was made in four databases taking into account variables such to identify the existing relationship between the metabolic syndrome and periodontal disease.Results: in total, 322 articles were found in the databases, using the descriptors. Of these, five articles met the inclusion criteria with a degree of coincidence of 66.6%. Of the 5 articles, two of them studied the influence of the metabolic syndrome on periodontitis by assessing variables such as furrow depth, bleeding to the catheter, Gingival index, bone resorption, plaque index, insertion loss-insertion level and other three articles Studied the influence of periodontitis on the metabolic syndrome taking into account variables such as the presence of microorganisms, glucose values, body mass index, blood pressure, triglycerides, high and low density lipoprotein (HDL-LDL), and inflammatory factors.Conclusion: the study established that the metabolic syndrome and periodontitis have a reciprocal relationship, since when the studies assessed the influence of MS on periodontitis or the influence of periodontitis on MS, in both situations, a close association was found between them when obtaining odd ratios (OR) higher than 1 in the influential variables.